Strategic management and automation of information units - Fernández Morales, Mynor (2012)
This article provides strategic guidance to prioritize which functions should be automated in a library, noting that today there is a rapid development of information technologies, coupled with increasing demand to automate the information units, with considering that resources are limited and must be allocated in the most effective and efficient manner. This provides effective guidance from the perspective of strategic management to help in where to allocate limited resources to automate the functions of the reporting unit, which will facilitate the achievement of its vision through a rational use of resources allocated. Although strategic planning has lost relevance in recent years, this is due to strategic plans often become documents that are archived on the shelves of organizations because they do not provide a clear method for implementing the strategies outlined in these patients. Thus here we introduce the Balanced Scorecard, which is a proven and useful to implement the strategies associated with strategic management, that facilitate the implementation and monitoring of strategies defined for the accomplishment of the mission/vision established for Information Unit.